The impact of maternal systemic diseases on the occurrence of cleft lip and palate in newborns: a narrative review - Sui, Hao; Du, Meijun; Chen, Jiali; Yang, Renjie; Shi, Bing; Huang, Hanyao; Wang, Yan (Frontiers in Public Health, 2025)
Cleft lip and palate (CLP) is a prevalent congenital anomaly of the maxillofacial region, characterized by abnormal openings in the lip or palate. This condition, affecting approximately 1 in 700 newborns globally, can manifest as cleft lip only, cleft palate only, or both. The etiology of CLP remains multifactorial, involving genetic and environmental influences, with maternal systemic diseases during pregnancy emerging as significant risk factors. Conditions such as circulatory disorders, endocrine and metabolic disorders, infectious diseases, and autoimmune diseases have been associated with increased CLP incidence. These maternal health issues can disrupt normal embryonic development, leading to cleft formation and affecting the child’s overall wellbeing, including feeding, speech, dental health, and psychological state. This review explores the relationship between maternal systemic diseases, including circulatory, endocrine and metabolic, infectious, and autoimmune disorders, and the occurrence of CLP in newborns. Understanding these connections is crucial for improving maternal health during pregnancy and reducing the risk of CLP, highlighting the importance of early monitoring and intervention.